Implementasi Model Problem Based Learning Bermediakan Slide Presentasi Berbasis Unjuk Kerja untuk Meningkatkan Kompetensi Pengetahuan IPA - I Md. Adi Arnawa (Jurnal Ilmiah Pendidikan Profesi Guru, 2021)
Science learning in elementary schools in achieving optimal knowledge competencies has not been carried out optimally. This study aims to analyze science knowledge competencies through the implementation of a problem-based learning model using performance-based presentation slides in online learning. This research is a classroom action research conducted in two cycles. The research subjects were students of class VIB, totaling 36 students. Science knowledge competency data were collected using tests. The collected data were analyzed by quantitative descriptive statistical analysis. The results showed that in the pre-cycle the average percentage of science knowledge competence was 64% categorized as low with classical completeness reaching 25%. After improving learning in the first cycle, the average percentage of science knowledge competence became 68% categorized as moderate with classical completeness reaching 67%. In the second cycle, it increased to 81% which was categorized as high with classical completeness reaching 83%. Based on the results of the study, it can be concluded that the implementation of the problem-based learning model using performance-based presentation slides in online learning can improve the scientific competence of class students.